Prosthodontic management of hypohidrotic ectodermal dysplasia: a case report - Bajraktarova Valjakova, Emilija; Misevska, Cvetanka; Korunoska Stevkovska, Vesna; Gigovski, Nikola; Sotirovska Ivkovska, Ana; Bajraktarova, Bona; Guguvcevski, Ljuben (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: Ectodermal dysplasia (ED) is a hereditary disorder associated with developmental disorders of two or more structures of ectodermal embryonic origin. Hypodontia or anodontia of the primary and permanent dentition, poorly developed alveolar ridgesand improper maxillo - mandibular relations, are the most common oral manifestations. Management of patients with ectodermaldysplasia requires a multidisciplinary team approach. Case presentation: A 6.5 year-old boy with hypohidrotic ectodermal dysplasia (HED) presented in this article, had typical featuresof HED: hypohidrosis, hypotrichosis, severe hypodontia, atrophic alveolar ridges, old-looking facial expression. According to thepatient’s age and clinical findings, removable complete over-denture prosthesis in both arches was the treatment of choice. Conclusion: In patients with ED, it is important to establish correct maxillo - mandibular relations and normal function of thedento-facial system (chewing, swallowing, and speaking). Prosthodontic treatment has a major impact on aesthetics and functions, facilitates psychological development and improves emotional condition and social life of the patient.